Anion‐Sorbent Composite Separators for High‐Rate Lithium‐Ion Batteries. Issue 21 (8th April 2019) - Zhang, Chen; Shen, Li; Shen, Jianqiang; Liu, Fang; Chen, Gen; Tao, Ran; Ma, Shengxiang; Peng, Yiting; Lu, Yunfeng
Abstract: Novel composite separators containing metal–organic‐framework (MOF) particles and poly(vinyl alcohol) are fabricated by the electrospinning process. The MOF particles containing opened metal sites can spontaneously adsorb anions while allowing effective transport of lithium ions in the electrolyte, leading to dramatically improved lithium‐ion transference number t Li + (up to 0.79) and lithium‐ion conductivity. Meanwhile, the incorporation of the MOF particles alleviates the decomposition of the electrolyte, enhances the electrode reaction kinetics, and reduces the interface resistance between the electrolyte and the electrodes. Implementation of such composite separators in conventional lithium‐ion batteries leads to significantly improved rate capability and cycling durability, offering a new prospective toward high‐performance lithium‐ion batteries. Abstract : An electrospun composite separator comprising metal–organic frameworks with open metal sites (OMSs) is developed for high‐rate lithium‐ion batteries, where the OMSs can efficiently immobilize anions in the electrolyte and afford highly mobile lithium ions. This work opens up new opportunities for functional separators aiming at regulating ion transport in the electrolyte and achieving a high rate capability of batteries.